Papel do córtex pré-frontal medial na ansiogênese induzida pelo estresse de derrota social em camundongos - Santos, Gabriel Victoriano dos (2018)
Recent findings have demonstrated that the medial prefrontal cortex (mPFC) has a lateralized role in the control of response to stressors, and the left hemisphere (LmPFC) would attenuate the anxiogenic responses elicited by right medial prefrontal cortex (RmPFC). The temporary chemical inactivation of LmPFC, followed by social defeat stress (SDS)provokes an anxiogenic effect that persists for up to 24 hours in mice. In the present study, we investigated: (1) the anxiety levels of mice exposed to the elevated plus maze (EPM) 2, 5 or 10 days after the combination SDS + LmPFC inactivation and (2) the role of the glutamate NMDA (n-methyl-D-aspartate) receptors located in the RmPFC in anxiety-related behaviors in mice exposed to the EPM two days after the combination “SDS + LmPFC inactivation”. Male Swiss mice received intra-LmPFC microinjection of saline or cobalt chloride (CoCl2, non-specific synaptic inhibitor) and were exposed to acute SDS or non-aggressive interaction. Two, five or 10 days later, they were exposed to the EPM to assess conventional anxiety [percentage of open arm entries and percentage of open arm time (%OE; %OT)] and complementary [Stretched attend posture frequencies in protected (pSAP) and unprotected (uSAP) places and protected Head-dipping (pHD) and unprotected (uHD) places] measures. Locomotor activity [frequency of closed-arms entries (CE)] was also recorded. The results showed that the association "inactivation of LmPFC + SDS" decreased %OE and %OT, increased pSAP and decreased uSAP and uHD in almost all testing days. In experiment 2, two days after receiving intra-LmPFC CoCl2 or saline + SDS, the animals received intra- RmPFC microinjection of saline or AP7 (NMDA receptor antagonist) 10 minutes before being exposed to the EPM. Results showed that the CoCl2 + SDS combination confirmed the anxiogenic effect, however only in the animals treated with saline in the LmPFC. CE was remained unchanged in both experiments. These results suggest that the inactivation of the LmPFC may prolong to up to 10 days the anxiogenic-like effects induced by SDS. Interestingly, this type of stress-induced anxiogenesis is impaired by the blockade of the NMDA receptor located in the RmPFC of mice.